PLURALITAS AGAMA MENURUT TOKOH-TOKOH AGAMA DAYAK - Hamid, Abdul (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2018)
Religious plurality is condition that no rejected by human. One thing that need is haow respond plurality that. So far recorded attitude that used by adherents religion in respond other religions in between exclusivism, inclusivism, and plurality. Exclusivism that known which claim absolute truth looked at no corresponding by current condition, thereby also which inclusivism that although no claim ownership absolute but tend see other religions as shadows from one religion, based weakness that owned by two attitude. Mode plurality appear as attitude that looked at corresponding for respond religious plurality. Like that there in village Kapul districts Halong regency Balangan. In this village there various kind of religion like religion of Islam, Kreisten Katolik, Hindu, Budha, and local religion.This research aim for known religion pluraly according to view religion figures Dayak in village Kapul districs Halong regency Balangan. This research is research qualitative by approach sociology use theory charismatic Max Weber. As for method this research is methd observation, directly plunge to field in Village Kapul districs Halong regency Balangan, interview, and documentation.This reaserch concluded that influence charismatic religions figures in Dayak religion when lead ritual event or in life daily has give harmonios life for people Dayak in districs Halong regency Balangan. So religion plurality in this village no make adherents religion Dayak other religion as people that intolerance.